Innovations in Biomedical Engineering - Gzik, Marek; Tkacz, Ewaryst; Paszenda, Zbigniew; Piętka, Ewa.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book presents the proceedings of the "Innovations in Biomedical Engineering IBE'2017" Conference held in Zabrze, Poland from October 19 to 20, 2017, and discusses recent research on innovations in biomedical engineering. The book covers a broad range of subjects related to biomedical engineering innovations. Divided into four parts, it presents state-of-the-art advances in: Engineering of biomaterials, Modelling and simulations in biomechanics, Informatics in medicine, and Signal analysis. By doing so, it helps bridge the gap between technological and methodological engineering achievements on the one hand and clinical requirements in the three major areas diagnosis, therapy and rehabilitation on the other.
Part I: Informatics in medicine -- Approach for spectrogram analysis in detection of selected pronunciation pathologies -- Automatic segmentation of lung cancer cells with the new parameters by using methods of image processing and analysis -- Breast Cancer Segmentation Method in Ultrasound Images.-  Detection and Tracking of the Biopsy Needle Using Ultrasound Images -- Detection of Wet Age-related Macular Degeneration in OCT Images: A Case Study -- Gender recognition using artiﬁcial neural networks and data coming from force plates -- Human Sperm Morphology Analysis using a Digital Holographic Microscope -- Idea and measurement methods used in bioimpedance spectroscopy -- Prototype measurement system for spatial analysis of speech signal for speech therapy -- Shear Wave Elastography and Strain Elastography: a Study on a Phantom.
Keywords: Computational intelligence; Biomedical engineering; Medical informatics; Artificial intelligence; Computational Intelligence; Biomedical Engineering and Bioengineering; Health Informatics; Artificial Intelligence